A case of reactive arthritis due to Clostridium difficile colitis - Alex C. Essenmacher; Nazish Khurram; Gregory T. Bismack (Greater Baltimore Medical Center, 2016)
Reactive arthritis is an acute, aseptic, inflammatory arthropathy following an infectious process but removed from the site of primary infection. It is often attributed to genitourinary and enteric pathogens, such as Chlamydia, Salmonella, Shigella, Campylobacter, and Yersinia, in susceptible individuals. An uncommon and less recognized cause of this disease is preceding colonic infection with Clostridium difficile, an organism associated with pseudomembranous colitis and diarrhea in hospitalized patients and those recently exposed to antibiotics. Recognition of this association may be complicated by non-specific presentation of diarrhea, the interval between gastrointestinal and arthritic symptoms, and the wide differential in mono- and oligoarthritis. We present the case of a 61-year-old, hospitalized patient recently treated for C. difficile colitis who developed sudden, non-traumatic, right knee pain and swelling. Physical examination and radiographs disclosed joint effusion, and sterile aspiration produced cloudy fluid with predominant neutrophils and no growth on cultures. Diagnostic accuracy is enhanced by contemporaneous laboratory investigations excluding other entities such as gout and rheumatoid arthritis and other infections that typically precede reactive arthritis. Contribution of Clostridium infection to reactive arthritis is an obscure association frequently difficult to prove, but this organism is warranted inclusion in the differential of reactive arthritis.